Actor–observer asymmetry in perceptions of parole board release decisions. Issue 5 (3rd September 2021) - Yelderman, Logan A.; Lawrence, Timothy I.; Lyons, Courtney E.; DeVault, Alicia
Abstract : In the current study, the actor–observer effect is tested with both mock parole board members and the public evaluating the responsibility of parole board members for a decision resulting in a parolee reoffending and committing a murder. Participants (two samples with a combined N = 1317) were randomly assigned to act as a mock parole board member and make a decision (which ended in the parolee reoffending) or as a member of the public who read a story about the same parole decision and outcome. Findings suggest that the traditional actor–observer asymmetry emerged across blame and responsibility concepts, emotion and moral judgments. Overall, the public held harsher judgments than the mock parole board members. Implications regarding self-enhancement, methodology and attribution theory are discussed.